A Behavioral Theory of Human Capital Integration - Jesper Christensen (Copenhagen Business School (CBS), 2018)
Human capital – the stock of knowledge and abilities possessed by employees – is consistently touted as an integral part of firm survival and success in dynamic environments. Managers must regularly decide how to allocate employees among competing tasks and projects to optimize the utilization of available knowledge, as well as select and implement the required structural mechanisms to support employees as they combine their knowledge to address complex problems on behalf of the firm. The principal motivation of this thesis is to explore how the effectiveness of particular aspects of organizational design in fostering the integration and use of human capital is bounded by individual cognitive limitations that may lead employees to deviate from expected behavior, both individually and in collaboration. The thesis consists of three research papers relying on comprehensive longitudinal project data from a global manufacturing company to investigate the integration of human capital and attendant consequences for firm performance. The first paper measures cognitive load as an outcome of managerial choices on employee allocation, and examines how cognitive load impacts employee choices on the distribution of working time among competing requirements. The second paper builds on these insights to explore how individuals adapt their information processing behavior in team settings based on cognitive load and the observed behavior of other team members, as well as how these adaptive processes and differences in cognitive load aggregate to impact team performance. The third paper investigates geographical and psychological distance between interdependent employees as important organizational design parameters that determine employee behavior and information use, both separately and in conjunction with one another. The overarching contribution of the thesis is to demonstrate, through the combination of psychological and organizational theory, how the ability of firms to properly activate and apply the knowledge held by their employees is fundamentally contingent on the interplay of cognitive limitations and managerial choices on organizational design. Common to the findings in this thesis is their immediate applicability in managerial and organizational settings as recommendations on how to allocate employees between competing uses. In sum, therefore, the thesis sketches the contours of a behavioral theory of human capital integration.
hdl:10398/9594
Keywords: 650